Performance analysis of charcoal barbeque set with an air ventilation system - Nur Fatimah, Mohd Yunus; Thorairajoo, Jhanani; Nadzirah, Mohd Mokhtar (2021)
The design of this air ventilation barbeque system is more efficient and user-friendly compared to the conventional barbeque set. A portable, easy to set up and flexible barbeque set for indoor and outdoor usage. It also improves barbeque quality by regulating the fitted blower attached to the barbeque set with a systematic air ventilation system. The meal needs less time to grill, and no manual fanning is needed.